Rapid solid-phase syntheses of a peptidic-aminoglycoside library. Issue 33 (16th August 2018) - Kukielski, Casey; Maiti, Krishnagopal; Bhaduri, Sayantan; Story, Sandra; Arya, Dev P.
Abstract: A library of mono- and di-amino acid peptidic-aminoglycosides (PAs), with kanamycin and neomycin as the model aminoglycosides, was systematically and rapidly synthesized via solid phase peptide synthesis. Aminoglycosides were first converted into N -Boc protected carboxylic acids and fifteen l -amino acids were then used in the diversification of the full library. The approach outlined describes a rapid synthetic procedure where >200 PA compounds can be synthesized in a few months with 85–95% purity. UV thermal denaturation assessed the binding stabilization by PAs to model human and bacterial A-site rRNA sequences. Significant differences were found in thermal melting profiles among PAs that were attributed to specific amino acid sequences. Neomycin PAs lead to a much larger variation in the stabilization of A-site rRNA sequences (ΔTm  = 2.6–17.1 °C) as compared to kanamycin PAs (ΔTm = 0.4–4.3 °C). Kanamycin PAs had little activity against Gram-negative and Gram-positive bacteria as compared with neomycin PAs that had significant antibacterial activity with MIC ranging from 2 to 16 μM. Graphical abstract: Image 1